Development of Low-Cost Deep Eutectic Solvents for CO2 Capture. (December 2017) - Ma, Chunyan; Sarmad, Shokat; Mikkola, Jyri-Pekka; Ji, Xiaoyan
Abstract: CO2 capture plays an important role to mitigate CO2 emissions. Deep eutectic solvents (DESs) as promising absorbents for CO2 separation have raised lots of attention. As a new class of ionic liquids (ILs), DESs maintain most of the favorite properties of ILs but avoid their economic and environmental problems. However, the viscosity of the synthesized DESs is relatively high, resulting in slow mass transfer rate (or slow sorption kinetics) and then may lead to a large equipment-size. The CO2 solubility in the DESs still needs to be improved. In our work, 35 DESs were prepared and screened in terms of their CO2 solubility and viscosity. Among them, 15 DESs with high CO2 solubility and low viscosity compared to the conventional ILs were chosen as the promising candidates. In addition, the effect of water as a co-solvent for the glycerol-based DES with relatively high viscosity was investigated, and two other DESs that demonstrated relatively high sorption capacity and low viscosity were chosen for functionalization to further improve their CO2 sorption capacity. The results showed that the viscosity decreased drastically from 716 to 20 mPa·s, while the CO2 solubility increased from 0.26 to 0.33 mol/kg DES by the addition of a small amount of water into the glycerol-based DES (BTMA/GLY (1:2)). The further increase of the amount of H2 O decreased the CO2 solubility due to the low CO2 solubility in H2 O. In addition, after functionalization of TPAC/ EA(1:4), the CO2 solubility increased from 1.4 to 3.2 mol/kg DES, which showed a better performance compared with the common ILs.